Accounting For Climate: The Role of Village Funds on Farmers' Income Using a Social and Cultural Approach - Yayan Sapitri; Mustamin; Abdul Kahar; Tenripada (Journal GoodWill, 2025)
This study examines the role of Village Funds in supporting farmers’ resilience to climate change and its implications for agricultural income using a social and cultural lens. Climate change has led to declining productivity, unstable harvest patterns, and reduced income for rural farming communities. Village Funds, as mandated through the State Budget (APBN), are designed to strengthen village development and community welfare, including climate adaptation efforts. This qualitative descriptive research was conducted in Kayu Jati Village, Ongka Malino Subdistrict, Parigi Moutong Regency, where the majority of residents depend on agriculture. Data were collected through interviews, field observations, and documentation involving farmers as key informants and village officials responsible for budget management. The study adopts Legitimacy Theory to explain how village governments justify fund allocation decisions in response to environmental and socio-cultural pressures. Findings indicate that Village Fund allocations for agriculture increased significantly between 2023 and 2024, reflecting a strategic shift toward climate-responsive programs. These programs include the construction and maintenance of farm access roads, provision of improved seeds and fertilizers, and farmer education on land use. The support of Gapoktan as a social institution also strengthens coordination and communication between farmers and the village government. Overall, Village Funds contribute positively to reducing farmers’ production costs, stabilizing income, and enhancing adaptive capacity to climate variability. The study highlights the importance of integrating climate accounting principles into village financial management to ensure sustainable agricultural development